2001
DOI: 10.1002/1097-4636(200111)57:2<258::aid-jbm1166>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylapatite binds more serum proteins, purified integrins, and osteoblast precursor cells than titanium or steel

Abstract: The implant material hydroxylapatite (HA) has been shown in numerous studies to be highly biocompatible and to osseointegrate well with existing bone; however, the molecular mechanisms at work behind this osseointegration remain largely unexplored. One possibility is that the implant, exposed to the patient's blood during surgery, adsorbs known cell adhesive proteins such as fibronectin and vitronectin from the serum. Osteoblast precursors could then adhere to these proteins through integrin-mediated mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
227
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(255 citation statements)
references
References 56 publications
12
227
0
5
Order By: Relevance
“…The results of QCM measurement shown in Fig.7 indicated that hydroxyapatite can absorb more serum proteins than titanium. Our results also conformed to a report that hydroxyapatite absorbed more cell attachment proteins such as fi bronectin, and vitronectin than pure titanium of the same roughness 30) . Because hydroxyapatite has stronger absorbability than titanium, the Ap disk could have gathered cell adhesion molecules on its surface even it was in serum-free medium, so that more cells adhered on the Ap disk than on the ti disk.…”
Section: Discussionmentioning
confidence: 99%
“…The results of QCM measurement shown in Fig.7 indicated that hydroxyapatite can absorb more serum proteins than titanium. Our results also conformed to a report that hydroxyapatite absorbed more cell attachment proteins such as fi bronectin, and vitronectin than pure titanium of the same roughness 30) . Because hydroxyapatite has stronger absorbability than titanium, the Ap disk could have gathered cell adhesion molecules on its surface even it was in serum-free medium, so that more cells adhered on the Ap disk than on the ti disk.…”
Section: Discussionmentioning
confidence: 99%
“…The major advantage for developing a composite material is the possibility of combining multiple properties associated with the natural tissue. While the polymeric network resembles the architecture of natural ECM, and hence acts as a supportive environment for cell functions (Drury and Mooney, 2003), homogeneously dispersed CaP nanoparticles render the resulting composite osteoconductive, encourage protein adsorption (Kilpadi et al, 2001) and increase matrix stiffness, thereby exerting strong effects on lineage specifi cation and commitment of naive mesenchymal stem cells (Engler et al, 2006).…”
Section: Biomimetic Modification Of Synthetic Hydrogels By Incorporatmentioning
confidence: 99%
“…Besides, the rutile-type oxide, which is formed on titanium as a titanium dioxide, is described as a stable crystalline form similar to ceramics in its bioreactive behaviour (Zhao et al, 2005). Although titanium has superior characteristics compared to other implant metals, the ostoconductivity of titanium is lower than calcium phosphate (CaP) based bioceramics (Kilpadi et al, 2001). Therefore, CaP based ceramics are referred to be bone-bonding materials, whereas titanium is a nonbonding material to bone (Hench & Wilson, 1984).…”
Section: Healing Around the Endosseous Implantmentioning
confidence: 99%
“…It has been well established that the Ca-P based coating of titanium favours the bone response compared with the uncoated titanium (Chang et al, 1999a;Wheeler, 1996). Additionally, Ca-P based surfaces bind more attachment proteins, such as fibronectin and vitronectin, for the integrin mediated binding action of osteoprogenitors compared to titanium surfaces (Kilpadi et al, 2001). Several techniques were described for the deposition of Ca-P coatings on titanium implants, including ion beam deposition, plasma spraying, sol-gel methods, laser deposition, radiofrequency sputtering, biomimetic deposition and electrostatic spray deposition (Ong & Chan 2000).…”
Section: Biomimetic Coating Of Titanium Surfaces With Calcium Phosphatesmentioning
confidence: 99%